2022
DOI: 10.3389/fnut.2022.992502
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Atractylodes macrocephala Koidz binding with zinc oxide nanoparticles: Characterization, immunological effect and mechanism

Abstract: Atractylodes macrocephala Koidz (A. macrocephala) has been used both as a traditional medicine and functional food for hundreds of years in Asia. And it has a variety of biological activities, such as enhancing the ability of immunity and modulating effect on gastrointestinal motility. In this study, a watersoluble polysaccharide with molecular weight of 2.743 × 10 3 Da was isolated from the root of A. macrocephala. Polysaccharide from A. macrocephala (AMP) consisted of arabinose, galactose, glucose, xylose, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…AMP-ZnONPs was prepared according to the protocol described in our previous study ( Bo et al, 2022 ). Chicken immunoglobulin G ( IgG ) ELISA kit was purchased from Shanghai Enzyme-linked Biotechnology Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMP-ZnONPs was prepared according to the protocol described in our previous study ( Bo et al, 2022 ). Chicken immunoglobulin G ( IgG ) ELISA kit was purchased from Shanghai Enzyme-linked Biotechnology Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed the potential of polysaccharides as immune adjuvants, enhancing both specific and non-specific immune responses when combined with vaccines ( Smith et al, 2023 ; Zhao et al, 2023 ). Polysaccharide from Atractylodes macrocephala Koidz binding with zinc oxide nanoparticles ( AMP-ZnONPs ), a novel compound obtained through reductive amination reactions in our lab, have shown potential in activating the immune functions of RAW264.7 cells and serving as vaccine adjuvants ( Bo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AMP-ZnONPs were prepared via the Borch reaction as previously described [14]. To prepare the H9N2 vaccine formulation, 1 mg/mouse of ZnONPs, 4 mg/mouse of AMP, 4 mg/mouse of AMP-ZnONPs and 5 µg/mouse of CT were mixed separately with 0.2 mL 10 −8.83 EID 50 /0.1 mL/dose of WIV, and the mixture was incubated for 24 h at 4 • C 10 rpm on a rotary mixer (MX-RD-Pro, DLAB, Beijing, China).…”
Section: Preparation Of Vaccinesmentioning
confidence: 99%
“…RNA extraction, cDNA synthesis and qRT-PCR were performed on samples of the jejunum as previously described [14]. Primer sequences GAPDH, α-chain, J-chain, polymeric immunoglobulin receptor (pIgR), IL-6, TNF-α, B-cell activating factor (BAFF), proliferation-inducing ligand (APRIL), CCR9 and CCL25 are listed in Table 3.…”
Section: The Expression Of Mrna Levels For Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation